Spontaneous left main coronary artery dissection complicated with vasospasm. Case resolution - Cátia Costa Oliveira (Permanyer, 2021)
CASE RESOLUTION We decided to end the procedure because the patient became asymptomatic and the ST-segment elevation resolved. After the procedure, the blood test performed revealed a new increase of troponin I levels (4.4 ng/mL). The patient started therapy with dihydropyridine calcium channel blockers due to the observed vasospasm. While in observation, the patient remained asymptomatic. Five days later, she was discharged on dual antiplatelet therapy. One month later, the patient was readmitted to undergo an elective coronary angiography to reassess the lesion. The coronary angiography only revealed the presence of irregularities without further lesions (videos 1 and 2 of the supplementary data). Therefore, the most probable diagnosis was a spontaneous coronary artery dissection (SCAD). The management of SCAD is still a matter of great discussion especially regarding left main coronary artery lesions and situations of hemodynamic instability as it is well-known that SCADs can heal spontaneously after 1 month.1-3 In this case, we decided not to proceed with the percutaneous coronary intervention because the patient became asymptomatic and the electrocardiographic alterations resolved after the administration of intracoronary nitrates and because we were not sure about the etiology of the severe vasospasm (SCAD vs atherosclerotic lesion). The reassessment coronary angiography performed...